Propaganda Blitz how the corporate media distort reality - Edwards, David 1962-; Cromwell, David 1962- (Pluto Press, 2018)
Shows that the corporate media does not just 'spin' the news--it fundamentally distorts everything it touches, hiding the real issues from public view, and often completely reversing the truth. Edwards and Cromwell uncover a storm of top-down campaigns behind war reporting from Iraq, Syria and Palestine, as well as the destruction of the credibility of figures on the left, including Jeremy Corbyn, Russell Brand and Hugo Chavez. Exposing propagandists at the top levels of the BBC, as well as their reporting on the Scottish independence referendum, the dismantling of the NHS and looming climate chaos, the authors explain the real meaning of 'objective' journalism, expose the fake news about 'fake news' and outline a model for anti-business media activism. --From publisher description